Consensus on Perioperative Transesophageal Echocardiography of the Brazilian Society of Anesthesiology and the Department of Cardiovascular Image of the Brazilian Society of Cardiology - Salgado-Filho,Marcello Fonseca (2018)
Abstract Through the Life Cycle of Intraoperative Transesophageal Echocardiography (ETTI/SBA) the Brazilian Society of Anesthesiology, together with the Department of Cardiovascular Image of the Brazilian Society of Cardiology (DIC/SBC), created a task force to standardize the use of intraoperative transesophageal echocardiography by Brazilian anesthesiologists and echocardiographers based on scientific evidence from the Society of Cardiovascular Anesthesiologists/American Society of Echocardiography (SCA/ASE) and the Brazilian Society of Cardiology.